Opodatkowanie fundacji i spółek - Małecki, Jerzy (Wydział Prawa i Administracji UAM, 1989)
A new phenomenon of recent years in Poland is the emergence of various foundations and partnerships conducting their economic activity in non-conventional forms and scopes. The article discusses numerous and complicated provisions regulating the taxation of foundations and partnerships in Polish law. The differences between the taxation of those two types of economic units follow from the character of those organizations. Tax preferences for foundations consist mainly in exemptions or reliefs in taxation of partnerships is highly diversified, for one may distinguish at least six ways of taxing their activity. The legal principle of equality of economic subjects, proclaimed in Art. 1 of the draft for the Act on Undertaking Economic Activity, is not adequately expressed in the present tax regulation, particularly as far as partnerships are concerned. Thus, it is necessary in the nearest future to reconstruct the Polish tax system. in the direction of creating the uniform tax system for all economic subjects,, neutral with respect to different forms of property.
Taxation of foudations and partnerships in polish law